The Problems of Investigating Crime in Subsidized Fuel Oil Type Bio Solar - Bibit Aris Yuliyanto (Jurnal Daulat Hukum, 2020)
. This study aims to analyze the role of investigators in handling crimes in the Oil and Gas / Subsidized Fuel Sector, especially the Bio-Solar Type in the Legal Area of the Central Java Regional Police and the obstacles faced and their solutions.The method used by researchers is a sociological juridical legal approach and the specifications in this study include descriptive analytical. Primary data were obtained from field studies interviews with investigators in the jurisdiction of the Central Java Regional Police.Based on the results of the study, it is concluded that the role of investigators in handling crimes in the Oil and Gas / Subsidized Fuel Sector, especially the Bio-Solar Type, is that they have carried out their duties in accordance with applicable regulations, from conducting investigations and investigations. Obstacles in Law Enforcement of the Crime of Misuse of Subsidized Fuel Type of Solar in the Central Java Regional Police, namely: a) lack of quality human resources; b) Lack of Facilities and Infrastructure; c) Difficulty in uncovering evidence; d) The amount of budget required in the Evidence Process. The solution is a) Organizing special learning activities for the Police; b) Fostering harmonious and kinship with the community, c) Forming a special team to spy on a place that is often used as a place for individuals who use subsidized fuel to buy diesel fuel.Keywords: Investigator, investigation, Crime, Fuel Oil.